2022
DOI: 10.1080/21655979.2022.2059960
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Eps15-homology domain-containing protein 2 induce resistance of renal cell carcinoma to sunitinib via microRNA-4731-5p/ABCF2 axis

Abstract: Circular RNAs (circRNAs) are linked with the occurrence and progression of renal cell carcinoma (RCC). However, circRNAs’ mechanism in developing resistance to RCC has not been clarified. This research assessed the role and mechanism of circular RNA circ Eps15-homology domain-containing protein 2 (EHD2) in the resistance of sunitinib (SU) to RCC. ACHN, 786-O, 769P, and HEK-293 T cells and RCC tissue samples were used for the investigations. The circEHD2 expression in RCC cells and tissues was determined throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These results indicated that circRNA_001895 promoted sunitinib resistance by regulating apoptosis and DNA damage repair (Tan et al, 2021). Additionally, as an upstream signal in the cirEHD2 (homology domain-containing protein 2)/miR-4731-5p/ABCF2 pathway, circEHD2 could cause sunitinib resistance by reducing the accumulation of drugs (Li et al, 2022).…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 90%
See 2 more Smart Citations
“…These results indicated that circRNA_001895 promoted sunitinib resistance by regulating apoptosis and DNA damage repair (Tan et al, 2021). Additionally, as an upstream signal in the cirEHD2 (homology domain-containing protein 2)/miR-4731-5p/ABCF2 pathway, circEHD2 could cause sunitinib resistance by reducing the accumulation of drugs (Li et al, 2022).…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 90%
“…Furthermore, the ABCB1 (1236C/T, 2677G/T and 3435C/T) polymorphisms influenced the transport capacity of P‐gp‐mediated sunitinib in the Caco‐2 cell line and enhanced resistance to sunitinib (Tan, 2020). And the ABC subfamily F member 2 (ABCF2) in this family subpopulation was demonstrated to participate in renal cell carcinoma tolerance to sunitinib by mediating the circEHD2/microRNA(miR)‐4731‐5p/ABCF2 pathway (Li et al, 2022).…”
Section: Molecular Mechanisms Of Sunitinib Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, owing to their unique circular structure, circRNAs exhibit characteristics of high conservation and stability, which make circRNAs promising biomarkers [ 5 ]. Emerging evidence has suggested that circRNAs are involved in the progression of various diseases, including cancer [ 6 8 ]. Until now, circRNAs have been demonstrated to play a vital oncogenic or anti-oncogenic roles in multiple cancers, including prostate cancer [ 9 ], breast cancer [ 10 ],colorectal cancer [ 11 ], and hepatocellular carcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 60 ] revealed that circRNA-001895 expression in tumor cells was related to sunitinib resistance in RCC and that hsa-circ-001895 regulated the downstream target gene FOX2 through miR-296-5P. Li et al [ 61 ] reported increased circEHD2 expression in sunitinib-resistant cell lines and tissues, which was linked to sunitinib resistance. Conversely, the knockdown of CircEHD2 reduced the progression of sunitinib-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%